To solve the equation \( x^2 - 18x = -80 \) and answer the parts step by step:
Part A:
To rewrite the equation as a perfect square trinomial, we want to complete the square.
- Start with the expression \( x^2 - 18x \).
- Take half of the coefficient of \( x \) (which is -18), square it, and add it to both sides. \[ \left(\frac{-18}{2}\right)^2 = 9^2 = 81 \] Therefore, we need \( c = 81 \).
The equivalent equation is: \[ x^2 - 18x + 81 = -80 + 81 \] This simplifies to: \[ x^2 - 18x + 81 = 1 \]
Part B:
Now, we can factor the left-hand side as a perfect square: \[ (x - 9)^2 = 1 \]
Part C:
To solve for \( x \) in the equation \( (x - 9)^2 = 1 \), we take the square root of both sides: \[ x - 9 = \pm 1 \] Solving these gives:
- \( x - 9 = 1 \) ⟹ \( x = 10 \)
- \( x - 9 = -1 \) ⟹ \( x = 8 \)
The lesser solution is \( x = 8 \).
Part D:
The greater solution is \( x = 10 \).
Summary of Answers:
- Part A: 81
- Part B: \( (x - 9)^2 = 1 \)
- Part C: 8
- Part D: 10